ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AGRESIVITAS PAJAK (Studi Empiris Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Netalia Theresa, 16.05.62.0034; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze and test the effect of liquidity, leverage, profitability, independent commissioner and capital intensity on tax aggressive. This study used a sample of 90 property and real estate companies listed on the Indonesia Stock Exchange for the period of 2014-2016. The sample of this study was obtained by purposive sampling. The type of data used is secondary data. Research data were analyzed by analysis of multiple regression and the data’s tabulation was processed by software SPSS 22.0 for windows. The results showed that leverage has a significant positive effect on tax aggressive, profitability and capital intensity have insignificant negative effect on tax aggressive, while the liquidity and independent commissioner have insignificant positive effect on tax aggressive. Keywords: liquidity, profitability, leverage, independent commissioner, capital intensity and tax aggressive